China’s live-streaming e-commerce market: A systematic review of its role in shaping global retail standards - Rolando, Benediktus (Communications in Humanities and Social Sciences, 2025)
This systematic literature review examines the burgeoning live-streaming e-commerce market in China, focusing on its rapid growth, the dynamics of consumer behavior and its global influence on retail standards. The key issues addressed in this study include the identification of the technological, social, and psychological factors driving this sector’s growth, the analysis of the impact of its interactive and immersive nature on consumer behavior and the exploration of its implications for the global retail landscape. Employing qualitative methods, the review synthesizes findings from 55 studies, selected through a systematic screening process. The findings of the study highlight that factors such as real-time interaction, social presence and streamers' influence significantly enhance consumer engagement and impulse buying tendencies. The Chinese model has set new benchmarks, showcasing innovative marketing strategies, technological integration and elevated consumer trust. These findings underscore the transformative potential of live-streaming e-commerce for future retail practices worldwide.